A Study on Eco-Friendly Cost-Effective Earthbag House Construction - Jain, Rajesh Kumar (Kathmandu University Journal of Science, Engineering and Technology, 2013)
This report will highlight the benefits both in terms of CO2 reduction and cost-saving construction. This project will develop rigorous assessment methods and broaden applications. It is expected that the project will have an impact on construction practice and lead to more research in this area. The weakest specimens tested obtained maximum compressive strengths ranging from 120 kN/m to 140 kN/m, almost 10 times as great as those typically achieved by conventional stud-frame housing in terms of load per meter of wall length. The lowest load deformation response was observed for the G9 specimen group, at 0.7 kN/mm. The strongest and stiffest results were observed for the 3-bag soil-filled specimen, with load deformation responses ranging from 8 kN/mm to 15 kN/mm, and compressive strength two orders of magnitude higher than conventional stud-frame housing, ranging from 1100 kN/m to 1300 kN/m. Strength and stiffness values for medium soil-filled specimens measuring 508 mm x 914 mm were in the same range as the values for the small specimens. There was little difference in stiffness between specimens filled with topsoil and those filled with a 4:1 ratio of topsoil to masonry sand, though a small sample size prevents a meaningful statistical analysis of the variance between the two fill materials.